Developing Beginning Design Students’ Self-Directed Learning Through Leadership Activity - Dorna Eshrati; Kerry L. Priest (Education Sciences)
In response to the growing demand for interdisciplinary leadership education within higher academia, this paper presents an action research initiative entitled “Who Am I and What Do I Do as a Designer?” The study involved 14 first-year environmental design and planning students, aiming to foster leadership qualities like independent thinking and self-reflection. The transformative process spanned several phases, including collaborative assignment statement development, design topic selection guided by a diagnostic survey, peer-coaching sessions for constructive feedback, active participation in the design process, and a culminating phase of meaningful self-reflection on their roles as designers. Initially faced with the challenging question of their identity as designers, the students ultimately created designs that authentically reflected their unique designer personas. Notably, 92% of students reported a stronger sense of identity as designers and 70% highlighted significant improvements in time management and planning. This work underscores the vital role of design education in not only honing technical and adaptive skills but also nurturing personal and leadership growth.